2006
DOI: 10.1159/000090386
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Adhesion Protein-1 in Atopic Eczema

Abstract: Background:Vascular adhesion protein-1 (VAP-1) is an adhesion molecule with an enzymatic activity which partakes in the migration process of lymphocytes. The aim of this study was to investigate VAP-1 expression in atopic eczema (AE) in comparison with healthy controls and psoriatic individuals. Material and Methods:Forty adult patients suffering from AE aged between 18 and 56 years were included in the study. The control group consisted of 35 healthy volunteers aged between 19 and 49 years and of 71 psoriatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Because sinusoidal endothelial cells in liver express VAP-1, which mediates binding of TILs to hepatocellular carcinoma, it is possible that VAP-1 participates in TIL homing [8]. Furthermore, the soluble form of VAP-1 (sVAP-1) is found in serum, which is believed to be derived from the membrane bound form, and which is elevated in certain diseases such as diabetes and some, but not all inflammatory diseases [9,10]. There is strong constitutive expression of VAP-1 on hepatic endothelia, and in inflammatory liver diseases, sVAP-1 is clearly elevated.…”
Section: Introductionmentioning
confidence: 99%
“…Because sinusoidal endothelial cells in liver express VAP-1, which mediates binding of TILs to hepatocellular carcinoma, it is possible that VAP-1 participates in TIL homing [8]. Furthermore, the soluble form of VAP-1 (sVAP-1) is found in serum, which is believed to be derived from the membrane bound form, and which is elevated in certain diseases such as diabetes and some, but not all inflammatory diseases [9,10]. There is strong constitutive expression of VAP-1 on hepatic endothelia, and in inflammatory liver diseases, sVAP-1 is clearly elevated.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were subsequently confirmed by additional investigators [48]. Most recently, other investigators have found an increased expression of yet another endothelial cell adhesion molecule -vascular adhesion protein-1, an adhesion molecule with an enzymatic activity which partakes in the migration process of lymphocytes -in the dermal microvascular endothelial cells of atopic patients, compared to normal individuals [49]. The latter finding provides additional support for the role of adhesion molecules in aiding the inflammatory process in atopic dermatitis and for the role of lymphocytes.…”
Section: Role Of Chemokines and Adhesion Moleculesmentioning
confidence: 66%
“…This control group is therefore different to the healthy controls described in the other studies [ 10 , 19 ], but more relevant as a comparator group with CRC patients. Increased levels of sVAP-1 have been reported in inflammatory diseases such as ectopic eczema [ 20 ], liver cirrhosis [ 11 ] and multiple sclerosis [ 21 ]. There is notably no increase in sVAP-1 levels in inflammatory bowel disease compared to healthy controls [ 22 ], despite increased tissue levels of VAP-1.…”
Section: Discussionmentioning
confidence: 99%